Geographical analysis of the characteristics of the natural water quality in the sea of Najaf and its impact on the development of fish farming (The Peerian Journal, 2025)
Fish wealth is an important part of agricultural and animal production and one of the main important pillars in the national economy and contributes to the national income by providing the food requirements of the population, but the work on the development of this sector is one of the necessary things to achieve self-sufficiency of fish products as well as providing the raw material for many food, food processing, agricultural, industrial, medical and therapeutic industries, so the quest for the development of the fish revolution reflects positively on other economic sectors, so research and study in this vital aspect of animal agricultural production (fish wealth) is of importance, especially specialized studies the study has taken the most important of these scientific problems, namely the problem of water and its natural qualitative characteristics that are underdeveloped and differentiated spatially and temporally, considering water as the environmental medium in which fish live and exercise all their effectiveness by studying the characteristics of water and its various qualities and its suitability for the growth and reproduction of fish in a wide aquatic environment located within the dry and semi-dry desert climate in the sedimentary plain area represented by a low Najaf ) in the province of Najaf .